The relevance of 'Wednesbury unreasonableness' in the light of 'proportionality' as a ground for judicial review - Varghese, Rajan (2014)
The principle of primary review and proportionality on the one hand and the principle of secondary review and Wednesbury reasonableness on the other hand gave a new dimension to Administrative Law, the former applying in the case of fundamental freedoms and the latter, in other cases. Proportionality as a legal test is capable of being more precise than a reasonableness test, besides requiring a more intrusive review of a decision made by public authority. Judicial verdicts have not openly held that the proportionality test may replace the Wednesbury test. Practically what is found is that the proportionality te3st is applied more and more, when there is violation of human rights and fundamental freedom and theWednesbury finds its presence more on the domestic law when there are violations of a citizens ordinary rights. - Reproduced.
Keywords: Administrative law; Judiciary